2014
DOI: 10.3389/fnhum.2014.00928
|View full text |Cite
|
Sign up to set email alerts
|

Gelotophobia and the Challenges of Implementing Laughter into Virtual Agents Interactions

Abstract: This study investigated which features of AVATAR laughter are perceived threatening for individuals with a fear of being laughed at (gelotophobia), and individuals with no gelotophobia. Laughter samples were systematically varied (e.g., intensity, laughter pitch, and energy for the voice, intensity of facial actions of the face) in three modalities: animated facial expressions, synthesized auditory laughter vocalizations, and motion capture generated puppets displaying laughter body movements. In the online st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 35 publications
4
22
1
1
Order By: Relevance
“…Past research has indicated that gender differences account for laugh‐related traits. Men had a stronger disposition to laugh at others than did women, but there were no gender differences with respect to gelotophobia and gelotophilia (Platt & Ruch, ; Platt, Ruch, Hofmann, & Proyer, ; Proyer, Hempelmann, & Ruch, ; Proyer & Ruch, ; Ruch et al, ; Ruch, Beermann, & Proyer, ; Ruch & Proyer, ). In addition, Chen and his colleagues analysed the impact of gender difference on laugh‐related traits among adolescents, that is, senior elementary students and junior high students, and found that boys had higher tendencies of katagelasticism and gelotophilia than did girls (Wang, ), which indicated gender differences with respect to laugh‐related traits for adolescents.…”
Section: Gender Differences On Laugh‐related Traitsmentioning
confidence: 97%
“…Past research has indicated that gender differences account for laugh‐related traits. Men had a stronger disposition to laugh at others than did women, but there were no gender differences with respect to gelotophobia and gelotophilia (Platt & Ruch, ; Platt, Ruch, Hofmann, & Proyer, ; Proyer, Hempelmann, & Ruch, ; Proyer & Ruch, ; Ruch et al, ; Ruch, Beermann, & Proyer, ; Ruch & Proyer, ). In addition, Chen and his colleagues analysed the impact of gender difference on laugh‐related traits among adolescents, that is, senior elementary students and junior high students, and found that boys had higher tendencies of katagelasticism and gelotophilia than did girls (Wang, ), which indicated gender differences with respect to laugh‐related traits for adolescents.…”
Section: Gender Differences On Laugh‐related Traitsmentioning
confidence: 97%
“…The latter were generally lower pitched, and shorter (but no differences in F0 were found). When comparing individuals with a fear of being laughed at to individuals with no fear, Ruch and colleagues [113] found within ILHAIRE that the fundamental frequency modulations and the variation in intensity were indicative of perceived maliciousness. Fast, non-repetitive voiced vocalizations, variable and of short duration were perceived as most friendly by individuals with a fear of being laughed at.…”
Section: Perception Of Acoustic Featuresmentioning
confidence: 99%
“…Similarly, Mancini et al [66] found that laypersons were generally very good in distinguishing full-body animations of laughter from non-laughter (79.70% of the stimuli were categorized correctly), with high levels of confidence in rating either stimulus category. When assessing the perceptions of gelotophobes and non-gelotophobes, Ruch and colleagues [113] found that in the virtual body portrayals (faceless full body stick figures), backwards and forward movements and rocking vs. jerking movements distinguished the most malicious from the least malicious laugh.…”
Section: Perception Of Bodily Portrayalsmentioning
confidence: 99%
See 2 more Smart Citations